The Treatment Of An Adult Patıent Wıth Severe Openbite By Means Of Extractıon, Vertıcal Chıncup And Modıfıed Kım Mechanıcs - Zafer Sarı; Bülent Çatalbaş (Galenos Yayinevi, 2002)
The aim of this study was to discuss the treatment results of an adult patient with skeletal and dental openbite malocclusion and dolicocephalic head type. The patient was treated with extraction therapy, modified Kim mechanics and vertical chincup. Openbite was closed with extrusion of incisors and passive intrusion of the molars. Besides, incisors were retruded, posterior teeth were mesialized and mandibular plane angle was slightly decreased. The results were stable at 18 month follow-up with only minor relapse.